ANALISIS KONTRIBUSI DAN EFEKTIVITAS PENDAPATAN ASLI DAERAH(PAD) PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA PEMATANGSIANTAR - Calen Calen; Henry Dunan Pardede (Jurnal Ekonomi dan Bisnis (EK&BI), 2019)
This study aims to determine the contribution and effectiveness of local taxes on Regional Original income in the city of Pematangsiantar. Pematangsiantar City is an autonomous region that does not have natural resources that can be exploited so that it requires creativity and innovation of local governments to be able to increase PAD from taxes which allows to increase Regional Original income in Pematangsiantar. In carrying out its functions as an autonomous region, regions must comply with existing regulations. including the consequences as a regional government, namely decentralization, which of course the financing aspec will also be decentralized.The research focused on using data from the Regional Revenue of Pematangsiantar in 2011-2016. From the results of the research conducted, it can be concluded that the contribution of each local tax post is still in the very poor category up to the lowest category, where the lowest local tax contribution to PAD is 0.05 percent up to the highest of 15.8 percent. While local tax collection has been effective with an average effectiveness rate of 90.39 percent per year.